Projeto de contenção de talude com cortina atirantada - Ferreira, João Victor [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This thesis has as goal doing a study of the development of hypothetical tied- back, applying the concepts of resistance of reinforced concrete, orestressed anchors and also involves soil properties. All of this to prevent the soil failure along a sloping surface. The method developed in 1957 by prof. Eng. Ântonio J. Costa Nunes, called “Brazilian Anchor Method” which encouraged the usage of this thype of method in Brazil. This assessment aims to highlight the main aspects of designing to be considered by the particularities of each material (reinforced concrete, prestressed steel and soil). This is demonstrated with a practical calculation example for designing a tied-back retaining wall. The work shows a sequence of objective calculations to be performed using the “Brazilian Anchor Method” to analyzing of the slope stability, guidelines for dimensioning anchors and to estimate the wall itself.

Este trabalho se trata de um estudo de desenvolvimento de uma cortina atirantada hipotética, aplicando os conceitos das propriedades de resistência do concreto armado com tirantes protendidos envolvendo o solo, como a base para ancoragem, com o intuito de impedir o escorregamento do maciço de terra. O Método Brasileiro de Atirantamento desenvolvido em 1957 pelo prof. Eng. Ântonio J. Costa Nunes, incentivou e difundiu o emprego desse tipo de análise no Brasil. Esse trabalho teve o intuito de evidenciar os principais aspectos desse método, por meio da investigação e descrição das especificidades de cada um dos materiais envolvidos (concreto armado, aço protendido e solos). Esses pontos são demonstrados a partir do desenvolvimento de um exemplo prático de dimensionamento de cortina, buscando elucidar de maneira objetiva a sequência de cálculos a ser executado, utilizando o método para análise de estabilidade, orientações das normas técnicas para dimensionamento dos tirantes e paramento.
Slope containment project with tied curtain
Keywords: Soil movement; Slope stability; Earth pressure; Retaining walls; Anchored wall; Movimento de solos; Taludes; Estabilidade de taludes; Muros de contenção; Cortinas atirantadas